iroda TYPOLOGY OF INTERACTIVE TASKS USING THE CAPABILITIES OF SOCIAL NETWORKS: TYPOLOGY OF INTERACTIVE TASKS USING THE CAPABILITIES OF SOCIAL NETWORKS - Kamolova, Iroda (Журнал иностранных языков и лингвистики, 2022)
One of the differences between interactive and active methods is the use of computer technology. Their use in education has led to changes in the content of methods of teaching foreign languages.